Pengembangan Sistem Manajemen Aset (Studi Kasus : RSUD dr. Iskak Tulungagung) - Gusna Ikhsan; Denny Sagita Rusdianto; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Assets are resources owned by a group as the effect of past events and the economic value of an asset is expected in the future. Economic value of an asset in the future is beneficial directly or indirectly to the interests of the group. Increase the number of assets requires asset management which has an effect on the use of assets, so that assets can be utilized optimally. The asset management cycle takes into account all risks from asset planning to asset elimination. Goal of asset management is to know the cheapest costs in a long period of time when determining the right policies in managing assets. To support good asset management, an asset management information system is needed. RSUD dr. Iskak is a B type hospital that located in Tulungagung. As a referral hospital, of course it has a lot of assets and have problems with asset management. The author took the initiative to develop an asset management information system to give solutions to the problems in RSUD dr. Iskak Tulungagung. A system developed based on a website with a prototype development model. Where in this study the final or final prototype was written. Post test is used to test the ease of operation of the system with the System Usability Scale approach with results of 71.5. These results represent systems that are developed into acceptable categories and in accordance with user expectations.